2019
DOI: 10.1146/annurev-micro-020518-115650
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Persisters and Infection: Past, Present, and Progressing

Abstract: Persisters are nongrowing, transiently antibiotic-tolerant bacteria within a clonal population of otherwise susceptible cells. Their formation is triggered by environmental cues and involves the main bacterial stress response pathways that allow persisters to survive many harsh conditions, including antibiotic exposure. During infection, bacterial pathogens are exposed to a vast array of stresses in the host and form nongrowing persisters that survive both antibiotics and host immune responses, thereby most li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
179
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(202 citation statements)
references
References 129 publications
2
179
0
1
Order By: Relevance
“…Bacterial persisters were first identified in 1944 by Joseph Bigger, who found that a small portion of Staphylococcus population was not killed by penicillin but still kept the susceptibility to the same antibiotic after re-growth [1]. Although bacterial persistence has been noticed for seven decades, it was appreciated only recently as one of the major causes of antibiotic recalcitrance and relapse of infection diseases [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial persisters were first identified in 1944 by Joseph Bigger, who found that a small portion of Staphylococcus population was not killed by penicillin but still kept the susceptibility to the same antibiotic after re-growth [1]. Although bacterial persistence has been noticed for seven decades, it was appreciated only recently as one of the major causes of antibiotic recalcitrance and relapse of infection diseases [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms, however, await further investigation. Bacteria, especially in biofilms, can develop persistent cells that are highly resistant to host immune attack, various environment stress and antibiotics [40][41][42][43][44]. Based on the results of the regrowth experiment of cells in the 10 −7 dilution of the 2.0, 1.0 and 0.50 µg/mL groups (Figure 7), we deduced that the lower the concentration of azalomycin F 5a used to treat S. aureus biofilms, the greater the proportion of persistent cells there would be.…”
Section: Discussionmentioning
confidence: 99%
“…Using just one antibody against one target, when bacteria secrete or have more than 200-400+ targets on their surface with presumed roles in virulence, may not be sufficient. Further, most approaches do not take into account that bacteria have different lifestyles, and therefore variable surface or secreted protein expression profiles, while residing within the host: vegetative, encapsulated or unencapsulated, biofilm associated, and intracellular, among others [46][47][48][49]. Finally, with respect to the mAb KB-001A, a diagnostic assay was not being used to properly identify patients with P. aeruginosa at the outset of the study.…”
Section: Previous Failures Lead To Current Successmentioning
confidence: 99%